2023
DOI: 10.1108/ijhma-08-2022-0114
|View full text |Cite
|
Sign up to set email alerts
|

The impact of immigration on urban housing prices in Indonesia

Abstract: Purpose Rural–urban migration has led to an increase in the community’s need for housing in the migration area. The demand for housing is getting higher while the land availability does not increase so that house prices will continue to increase. This study aims to estimate the impact of immigration on urban housing prices in Indonesia. Design/methodology/approach This study examines the effect of immigration on urban housing prices at the city level in Indonesia by using 14 major cities data from 2012 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…The band combination used in this algorithm is the blue-green band combination which has a wavelength of 410 -500 nm and 500 -610 nm. These results align with the research of [19] who reported that the correlation coefficient value of the blue band ratio with the green band is much higher than the ratio of other band combinations. Other researchs conducted by [20,21,22,23] also reported that the combination of blue band and green band in Sentinel-2A image has excellent penetration among other band combinations in mapping bathymetry.…”
Section: Bathymetry Algorithmssupporting
confidence: 92%
“…The band combination used in this algorithm is the blue-green band combination which has a wavelength of 410 -500 nm and 500 -610 nm. These results align with the research of [19] who reported that the correlation coefficient value of the blue band ratio with the green band is much higher than the ratio of other band combinations. Other researchs conducted by [20,21,22,23] also reported that the combination of blue band and green band in Sentinel-2A image has excellent penetration among other band combinations in mapping bathymetry.…”
Section: Bathymetry Algorithmssupporting
confidence: 92%